ANALYSIS OF THE IMPACT OF SOCIAL MEDIA ON THE POLITICAL PARTICIPATION OF INDONESIAN YOUTH IN THE PERSPECTIVE OF DEFENSE MANAGEMENT - Nafita Rizqiyatul Azkiya; Jonni Mahroza; Agung Rishdianto; Hikmat Zakky Almubaroq (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Today, social media is the most powerful tool for exchanging information. The percentage of people using the Internet is increasing according to the We Are Social study from January 2021. The participation of the younger generation brings new perspectives, fresh ideas, and enthusiasm that can revive democracy. Through their political participation, young people can help build a more inclusive and sustainable society. The ease of access to information through social media shows that there is a process of democratization through the fulfillment of human rights. However, if freedom of expression is not accompanied by tolerance and individualism, it will create a crime that can threaten the defense of the Indonesian nation. The purpose of writing this journal is to find out the role of social media in political participation and the positive-negative impacts of social media on the political participation of Indonesia's young generation in defense management. This research uses a qualitative approach that uses language for cases and contexts, examines social processes and cases in their social context, and looks at the interpretation or creation of meaning in certain settings. For the millennial generation, social media is considered of presenting a new way of communicating. Social media is starting to be used intensively in political aspects by having a more specific context. In public, social media is used as a new medium to express political participation, while for politicians themselves social media is a new means of establishing communication, building interaction, and disseminating political information. The role of social media in political participation is very large and everything can be achieved easily through social media. However, behind the large positive impact of social media on participation in politics, there are also negative impacts that are no less large and can even backfire on the political participants themselves.